Prevalence of Non-tuberculous Mycobacteria (NTM) in Surakarta, Indonesia: Higher Than Expected - Saptawati, L; Kusumo, H; Suryawati, B (KnE Life Sciences, 2019)
The incidence and prevalence of infection due to non-tuberculous mycobacteria (NTM) species are increasing worldwide and rapidly becoming a major public health problem. Despite increasing knowledge about NTM, there are still many challenges in diagnostic tools and treatment for this infection. Indonesia is ranked number two for tuberculosis infections; however, there is a lack of data about NTM infection. The aim of this study was to analyze the prevalence of the detection of NTM from sputum specimens of pulmonary tuberculosis suspects in a lung hospital center in Surakarta, Central Java, Indonesia. This study was a retrospective study which analyzed the laboratory data obtained from a lung hospital (Balai Besar Kesehatan Paru Masyarakat / BBKPM), in Surakarta, Indonesia. Samples were collected from patients with tuberculosis and cases with a presumptive diagnosis of tuberculosis from January 2013 to December 2017. All sputum samples were stained for microscopic analysis and were also incubated for the detection of mycobacterial growth in Lowenstein Jensen (LJ) medium and in LJ medium with the addition of para-nitrobenzoic acid (LJ-PNB) to identify Mycobacterium tuberculosis (MTB) or NTM strain. Biochemistry test, Niacin test, was used to confirm NTM strain. For five year periods, there were 9,284 patients samples were cultured to detect MTB infection. For all the sputum samples, 1,974 samples (21.3%) were cultured positive; out of the positive samples 1,636 (85%) were MTB strains and 334 (15%) were NTM strains. The data revealed that NTM infection cases were more likely to have been diagnosed aged older than 35 years (72%). This study showed that there was a high number of NTM infection detected in patients with presumptive diagnosis of tuberculosis. Therefore, another approach should be conducted to provide effective therapy for infection due to NTM. Identification of NTM in species level will be important to provide empirical therapy for this infection.